Difficulties of Cataract Surgery in Lens-Induced Glaucoma Due to Subluxated Cataract - Meidiana Devira Aristanti; Nurwasis; Jamaluddin (Vision Science and Eye Health Journal, 2023)
Introduction: Cataract is a disease of the eye in which the normal clear lens has opacified and obscured the passage of light. A mature cataract occurs when the lens is opacified. Lens subluxation is a condition when the crystalline lens is not in its anatomical position that can result in decreased anterior chamber depth. It is a potentially high risk of developing pupillary block, leading to lens-induced glaucoma (secondary angle closure glaucoma). In this case, the definitive therapy is lens extraction, which is challenging for cataract surgeons. This case report aims to expose the difficulties of cataract surgery in lens-induced glaucoma due to subluxated cataract. Case Presentation: A 56-year-old male presented with unable to see in his right eye, followed by foggy vision, glare when seeing the light, and a history of an acute glaucoma attack. His right best corrected visual acuity (BCVA) was 1/300, and the intraocular pressure (IOP) was 5 mmHg on therapy with glaucoma medications. Slit lamp examination of the right eye showed a shallow anterior chamber, irradiated iris, mid-dilated pupil, completely cloudy lens, and a capsular instability around 12 to 6 clock hours (180°/2 quadrant). This patient was diagnosed with mature cataract and lens-induced glaucoma due to subluxated mature cataract and was given glaucoma medications also underwent phacoemulsification (PE) along with Intraocular lens (IOL) and capsular tension ring implantation due to the lens instability and excessive lens movement. Conclusions: Cataract surgery for subluxated mature cataract and lens-induced glaucoma is challenging because of the shallow anterior chamber, capsular instability, and excessive lens movement. A thorough diagnosis, preoperative evaluation, postoperative monitoring, and evaluation are essential for safe cataract surgery, reducing the risk of complications and achieving a good result.